2014
DOI: 10.1371/journal.pone.0100249
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Cell Heterogeneity in Small Cell Lung Cancer (SCLC): Phenotypical and Functional Differences Associated with Epithelial-Mesenchymal Transition (EMT) and DNA Methylation Changes

Abstract: Small Cell Lung Cancer (SCLC) is a specific subtype of lung cancer presenting as highly metastatic disease with extremely poor prognosis. Despite responding initially well to chemo- or radiotherapy, SCLC almost invariably relapses and develops resistance to chemotherapy. This is suspected to be related to tumor cell subpopulations with different characteristics resembling stem cells. Epithelial-Mesenchymal Transition (EMT) is known to play a key role in metastatic processes and in developing drug resistance. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
59
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(65 citation statements)
references
References 40 publications
5
59
1
Order By: Relevance
“…However, in a recent study Krohn et al demonstrated that several SCLC cell lines comprise a small subpopulation of adherent cells which express high levels of the mesenchymal markers vimentin and fibronectin and very low levels of the epithelial markers E-cadherin and Zona Occludens 1 (ZO-1). 35 Although primary tumors and CTCs present EMT features in most tumors, distant metastases are generally epithelial in morphology. In 2002, Jean Paul Thiery, proposed the reversible EMT metastasis model in which tumor cells activate EMT to invade, while, upon arriving at distant sites, they undergo a reversion process, or MET, to form epithelial metastases.…”
Section: Resultsmentioning
confidence: 99%
“…However, in a recent study Krohn et al demonstrated that several SCLC cell lines comprise a small subpopulation of adherent cells which express high levels of the mesenchymal markers vimentin and fibronectin and very low levels of the epithelial markers E-cadherin and Zona Occludens 1 (ZO-1). 35 Although primary tumors and CTCs present EMT features in most tumors, distant metastases are generally epithelial in morphology. In 2002, Jean Paul Thiery, proposed the reversible EMT metastasis model in which tumor cells activate EMT to invade, while, upon arriving at distant sites, they undergo a reversion process, or MET, to form epithelial metastases.…”
Section: Resultsmentioning
confidence: 99%
“…More generally, the transition from a neuroendocrine state to a state where neuroendocrine differentiation is decreased but neuronal differentiation is increased may be related to the exceptional plasticity of SCLC cells (reviewed in (Yuan et al , 2019)). Epithelial-to-mesenchymal transition (EMT) is thought to contribute to migration, metastasis, and resistance to treatment in many cancer contexts and may play a role in SCLC (Allison Stewart et al , 2017, Krohn et al , 2014, Canadas et al , 2014, O’Brien-Ball and Biddle, 2017, Singh and Settleman, 2010). Vascular mimicry (or epithelial-to-endothelial transition (EET) (Yuan et al , 2019)) may also contribute to tumor growth and response to treatment in SCLC (Williamson et al , 2016).…”
Section: Discussionmentioning
confidence: 99%
“…However, in the current study, as well as several previous studies, we identified the complexity of lung CSCs and thus highlight the difficulties that need to be dealt with before proceeding towards clinical application 18 . The presence of intra-tumor heterogeneity and inter-tumor phenotypic heterogeneity have been long described in general for cancer, particularly lung cancer 33 - 35 . Thus, it is likely that the specificity and sensitivity of markers used for lung CSC identification will vary with tumor type (adeno, squamous, small cell), stage, genetic signature and other phenotypic determinants.…”
Section: Discussionmentioning
confidence: 99%